Experimental and Theoretical Analysis of Throughput of MIMO PLC Network - Abdelmounim Hmamou; Mohammed El Ghzaoui; Jaouad Foshi; Jamal Mestoui (Journal of Engineering and Technological Sciences, 2022)
In this study, we mainly focused on a theoretical analysis of HomePlug 1.0 and an experimental analysis of modem data rates through a section of a PLC network with several configurations. We introduce the utilization of the MIMO technique to increase the throughput over a PLC channel. Besides, we propose a MIMO PLC channel model to evaluate the channel transfer function of MIMO PLC. We used an equivalent per-unit-length model of the indoor power line network to characterize the three-conductor cable. Based on this mathematical model, we analyzed the throughput of the PLC network with different household appliances. The equivalent circuit of each appliance is also given. The simulation results showed that the throughput is influenced by household appliances connected to the sockets of a MIMO PLC network. Moreover, we also compared the throughput between single and multi-antenna systems. Based on the simulation results, we found that the data rate increased with frequency. In addition, the performance of the MIMO PLC system was almost 90% higher than that of a SISO PLC system in terms of channel capacity.